Depression in medical studients - Barakoti, B (Journal of Kathmandu Medical College, 2012)
DOI: http://dx.doi.org/10.3126/jkmc.v1i1.7256 Journal of Kathmandu Medical College, Vol. 1, No. 1, Issue 1, Jul.-Sep., 2012 pp.45-46